Entrepreneurial activity and economic growth: A dynamic data panel analysis of European countries - Sofia Gomes; Pedro Ferreira (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The goal of this article is to analyse the impact of different measures of entrepreneurial activity, namely through attitudes and behaviour, on the economic growth of 21 European countries. The goal is to assess the impact of entrepreneurial activity, measured by perceived capabilities, perceived opportunities, entrepreneurial activity, and total early stage, on the economic growth of these countries. Research Design & Methods: This study is based on a quantitative methodology and uses a data panel covering 21 European countries and a period from 2001 to 2019 (196 observations). A statistical analysis of the dependent, independent and control variables was performed, panel data stationarity analysis was carried out, and three multiple linear regression models were estimated using the generalized method of moments (dynamic panel data). Findings: The results suggest that the entrepreneurial activity driven by the opportunity has a positive impact on the gross domestic product per capita and, as such, stimulate the economic growth of the European countries considered in this sample. However, entrepreneurial activity at an early stage and the skills and knowledge to start a new business have a negative impact on the economic growth of these countries. Implications & Recommendations: In general, this study suggests that entrepreneurship driven by opportunity (directly or indirectly by perceived capacities) is a key factor in stimulating the European countries' economic growth considered in this sample. Contribution & Value Added: This study complements the existing literature that analyses the impact of entrepreneurship on economic growth, but using a sample of countries in Europe (there are few empirical studies for this purpose on European countries), and it is innovative because three different measures of entrepreneurial activity are tested, a more generic one and two other measures of entrepreneurial behaviour and attitudes collected by the global entrepreneurship monitor (GEM) to assess their impact of entrepreneurship on countries' economic growth.
Keywords: L26; O47; O52; 330; perceived capacity; perceived opportunity; entrepreneurship; economic growth; European countries